The impact of the COVID-19 crisis on European businesses: Evidence from surveys in Austria, Germany and Spain - Raquel García; Christian Gayer; Werner Hölzl; Sergio Payo; Andreas Reuter; Klaus Wohlrabe (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This note presents the results of two ad-hoc questions on the impact of the corona-crisis, which were included in the April-wave of the European Commission's Joint Harmonised EU Programme of Business Surveys. The questions were asked to German, Spanish and Austrian firms in the industry, services, retail trade and construction sectors and focused on the effect of the crisis on expected annual turnover and the ability of firms to survive in the presence of the prevailing confinement measures. The results illustrate the sweeping effect of the crisis on firms' turnover and provide alarming figures on a potential insolvency/bankruptcy wave caused by the current confinement measures.
Keywords: 330; Coronavirus; Krisenmanagement; Insolvenz; Deutschland